IMPROVEMENT OF INSURANCE ACTIVITIES OF AGRICULTURAL ENTERPRISES - Yadgarov Akram (Scholar Express Journals, 2024)
The agricultural sector of the economy is characterized by the seasonal nature of production activities and a large capital intensity. The material and technical resources used in economic activity have a low level of mobility, and the results of production and economic activity are highly dependent on natural and climatic conditions, the duration of the production cycle can last for several months. This determines the need for agricultural insurance. The rhinestone protection makes it possible to financially stabilize the income level of agricultural enterprises and can serve as an alternative to lending and subsidizing agriculture. In agricultural production, weak and small enterprises are most exposed to risks. The presence of state support for such enterprises, in our opinion, violates the principle of free competition and prevents the attraction of effective investors to the agricultural sector. We believe that the state in the agricultural sector of the economy should primarily support investment risk insurance, this will allow for a more rational use of public funds allocated to support agriculture, and attract investors ' funds to the industry.
Keywords: agricultural sector; agricultural insurance; income level of agricultural enterprises